2008
DOI: 10.1111/j.1539-6924.2008.01010.x
|View full text |Cite
|
Sign up to set email alerts
|

Personal Efficacy, the Information Environment, and Attitudes Toward Global Warming and Climate Change in the United States

Abstract: Despite the growing scientific consensus about the risks of global warming and climate change, the mass media frequently portray the subject as one of great scientific controversy and debate. And yet previous studies of the mass public's subjective assessments of the risks of global warming and climate change have not sufficiently examined public informedness, public confidence in climate scientists, and the role of personal efficacy in affecting global warming outcomes. By examining the results of a survey on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

25
432
13
5

Year Published

2010
2010
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 697 publications
(512 citation statements)
references
References 54 publications
(68 reference statements)
25
432
13
5
Order By: Relevance
“…Instead, motivation for the behavior is a necessary precursor for actual behavior change consistent with the information-motivation-behavioral skills model, in which knowledge and motivation both influence behavior (Fisher et al 1994;Fisher and Fisher 1992). More recent work found that knowledge does not consistently influence behavior (Misovich et al 2003) corroborated by other studies in a climate change context such as Kellstedt et al (2008) who find that climate change knowledge actually makes people less concerned and likely to act.…”
Section: Factors Affecting Stated and Actual Adoptionsupporting
confidence: 60%
“…Instead, motivation for the behavior is a necessary precursor for actual behavior change consistent with the information-motivation-behavioral skills model, in which knowledge and motivation both influence behavior (Fisher et al 1994;Fisher and Fisher 1992). More recent work found that knowledge does not consistently influence behavior (Misovich et al 2003) corroborated by other studies in a climate change context such as Kellstedt et al (2008) who find that climate change knowledge actually makes people less concerned and likely to act.…”
Section: Factors Affecting Stated and Actual Adoptionsupporting
confidence: 60%
“…Although it may be appropriate to criticize the media for not presenting the case for climate change more strongly and for not presenting the implications of individual behavior more clearly (28), scientists share at least some of the responsibility for the current state of affairs. For example, Fischhoff (29) recently argued that scientists may have failed the public by not providing information in a credible and comprehensible manner to facilitate better climate-related decisions.…”
Section: Discussionmentioning
confidence: 99%
“…The public's issue with science is not necessarily ignorance (7). The public increasingly knows more than before about climate change's causes (8).…”
Section: Public Beliefs and Affectmentioning
confidence: 99%